3 and Analysis of the Quality of live of Chilcren and Teenagers in Oncological Treatment in the Municipality of Montes Claros-MG - Paranhos Magalhães, Nathália; Veloso Pereira, Gustavo; Godinho Gonçalves, Romeu; Lancuna, Alex Cezar; Andrade Ferreira, Bianca; Prates Eleutério, Sabrina Jeane (Revista Unimontes Científica, 2020)
This work aims to analyze the quality of life of children and teenagers in oncological treatment registered at the Fundação Sara Albuquerque Costa, a reference center in the northern region of the State of Minas Gerais, Brazil, located at in the city of Montes Claros. Methods: This is a descriptive, prospective, and transversal investigation. It consisted in the implementation of the questionnaire “Pediatric quality of life cancer module (PedsQL)” in order to analyze the impact of therapeutic procedures, symptomatology, collateral and toxic effects, social changes, and aspects of the daily and psychological routine upon the quality of life of these patients. Results: This study found that many times children and teenagers in oncological treatment present some special difficulties. Most of them experienced nauseas during the treatment and, specifically regarding certain situations. One of the great fears of these children is related to the needles and injections they frequently have to deal with. Further, half of the participants reported that, with a certain frequency, they do not consider themselves attractive. Conclusion: The importance of adopting measures and actions that might reduce the anxiety and fear experienced by children and teenagers is highlighted in this investigation, therefore contributing to the improvement of the quality of life.